Ekstrak biji kesumba keling (Bixa orellana L.) sebagai uji indikator alternatif titrasi asam basa - Khairunnisa, Khairunnisa; Putri, Safridha Kemala; Erlinawati, Erlinawati (JoMLaT (Journal of Medical Laboratory Technology), 2024)
One of the plants that can produce color is kesumba rivet with the Latin name (Bixa orellana L.). As a natural dye, the pigment of kesumba keling (Bixa orellana L.) seed extract contains bixin and norbixin which are thought to change color in acid-base conditions, therefore this research aims to find out whether kesumba keling (Bixa orellana L.) seed extract can used as an alternative indicator in acid-base titrations. This research is using experimental method. The sample in this study was kesumba keling seeds (Bixa orellana L.). From the research results, it is known that kesumba keling seed extract (Bixa orellana L.) experiences color changes that are not clearly visible in acidic or alkaline conditions because the color change is too slight so it is difficult to determine the end point of the titration. So it can be concluded that kesumba keling (Bixa orellana L.) seed extract cannot be used as a substitute for natural indicators in acid-base titrations.